Revolution : Art of the Sixties from Warhol to Beuys. - Bremner, Ann; Gould, Claudia; Kamon, Yasuo; Shioda, Junichi; Thompson, Jon; Watanabe, Yohko (Tokyo : Museum of Contemporary Art, 1995)
Andre, Carl ; Anselmo, Giovanni ; Arman ; Art & Language ; Artschwager, Richard ; Baldessari, John ; Baselitz, Georg ; Beuys, Joseph ; Blake, Peter ; Bourgeois, Louise ; Broodthaers, Marcel ; Buren, Daniel ; Christo ; de Maria, Walter ; Dine, Jim ; Fabro, Luciano ; Flanagan, Barry ; Riverhead (New York) ; Fulton, Hamish ; Gilbert & George ; Haacke, Hans ; Hains, Raymond ; Hamilton, Richard ; Hesse, Eva ; Hockney, David ; Judd, Donald ; Kawara, On ; Kelly, Ellsworth ; Klein, Yves ; Kosuth, Joseph ; Kounellis, Jannis ; Kudo, Tetsumi ; Kusama Yayoi ; LeWitt, Sol ; Lichtenstein, Roy ; Long, Richard ; Manzoni, Piero ; Marden, Brice ; Merz, Mario ; Morris, Robert ; Nauman, Bruce ; Oldenburg, Claes ; Ono, Yoko ; Paik, Nam June ; Penck, A.R. ; Paolozzi, Eduardo ; Polke, Sigmar ; Richter, Gerhard ; Rosenquist, James ; Rotella, Mimmo ; Ruscha, Edward ; Ryman, Robert ; Segal, George ; Serra, Richard ; Smithson, Robert ; Stella, Frank ; Tinguely, Jean ; Warhol, Andy ; Weiner, Lawrence ; Wesselmann, Tom
Revolution : Art of the Sixties from Warhol to Beuys, Museum of Contemporary Art, Tokyo, September 30 - December 10, 1995
English-Japanese
kunstcatalogus
Keywords: Amerika